Analyzing the acoustic behavior of gamelan music performance in different environments - Dhea Amanda Septiawati; Shalika Nurul Aulia (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
This study examines the acoustic characteristics of Gamelan music performances in various settings, explicitly emphasizing the disparity between enclosed auditoriums and open spaces. Given the growing frequency of Gamelan performances in varied contexts, the comprehension of how diverse environments impact acoustic qualities is of utmost importance to enhance audience experience and safeguard the authenticity of traditional musical forms. The significance of this study arises from the increasing prevalence of Gamelan music in non-traditional contexts, such as outdoor festivals, prompting inquiries into the variations in acoustic properties across different situations. This research endeavor aims to fill the existing gap in knowledge by undertaking a qualitative examination of acoustic phenomena in enclosed and unobstructed environments. The research presented in this study is notable for its extensive investigation into acoustic phenomena across many settings, considering several aspects, including sound reflection, absorption, and reverberation. Qualitative analytical techniques were applied to evaluate the acoustic characteristics within each respective setting by utilizing a comprehensive examination of pertinent scholarly works pertaining to acoustics and Gamelan music. The findings suggest that closed auditoriums, which have controlled sound distribution and little interference, exhibit unique acoustic characteristics compared to open spaces. In open spaces, sound propagation is affected by ambient elements and the audience's presence. The research underscores the significance of architectural design in influencing acoustic surroundings and the necessity for flexible performance venues that can handle the intricacies of Gamelan music. This study makes a valuable contribution to the existing body of knowledge by providing a more comprehensive understanding of the impact of contextual elements on the acoustic characteristics of Gamelan music. The findings of this research have implications for the improvement of performance venues and the promotion of audience involvement in various contexts.